The Usage of the Bible in African Missionary History.: The Legacy of the New Testament usage in Africa - Anum, Eric (Ghana bulletin of theology, 2006)
An issue that is closely related to the approaches and methodologies to biblical interpretation in Africa is the use of the Bible in missionary history. Through the decades, there have been the introduction, translation, exegesis and usage of the Bible by European missionaries who were the carriers of Christianity to Africa. This article explores the possible theological baggage that was left behind by Western missionaries that worked in selected parts of Africa.